Isolation and functional analysis of a cDNA encoding a myrcene synthase from holm oak (Quercus ilex L.) - Fischbach, Robert J.; Zimmer, Wolfgang; Schnitzler, Jörg-Peter (European Journal of Biochemistry, 2001)
An 859-bp cDNA segment of a terpene synthase gene was amplified by PCR from the evergreen sclerophyllous holm oak (Quercus ilex L.) using heterologous primers for conserved regions of terpene synthase genes (TPS) in dicotyledonous plants. Based on the sequence of this segment, homologous primers were designed for amplification by RACE-PCR of a cDNA segment carrying the monoterpene synthase gene myrS. The gene encodes a protein of 597 amino acids including an N-terminal putative plastid transit peptide. The gene without the segment encoding the transit peptide was cloned by PCR into a bacterial expression vector. Expression in Escherichia coli yielded an active monoterpene synthase, which converted geranyl diphosphate (GDP) predominantly into the acyclic monoterpene myrcene and to a very small extent into cyclic monoterpenes. Sequence comparison with previously cloned monoterpene synthases revealed that the myrcene synthase from Q. ilex belongs to the TPSb subfamily.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: functional expression; geranyl diphosphate; monoterpene synthases; myrcene synthase; Quercus ilex

Isolation and functional analysis of a cDNA encoding a myrcene synthase from holm oak (Quercus ilex L.) (European Journal of Biochemistry, 2001)
An 859-bp cDNA segment of a terpene synthase gene was amplified by PCR from the evergreen sclerophyllous holm oak (Quercus ilex L.) using heterologous primers for conserved regions of terpene synthase genes (TPS) in dicotyledonous plants. Based on the sequence of this segment, homologous primers were designed for amplification by RACE-PCR of a cDNA segment carrying the monoterpene synthase gene myrS. The gene encodes a protein of 597 amino acids including an N-terminal putative plastid transit peptide. The gene without the segment encoding the transit peptide was cloned by PCR into a bacterial expression vector. Expression in Escherichia coli yielded an active monoterpene synthase, which converted geranyl diphosphate (GDP) predominantly into the acyclic monoterpene myrcene and to a very small extent into cyclic monoterpenes. Sequence comparison with previously cloned monoterpene synthases revealed that the myrcene synthase from Q. ilex belongs to the TPSb subfamily.